Physics - Breithaupt, Jim (Macmillan foundations, 1999)
This text aims to fill a gap in the market for a broader based text which caters for a wide range of science students who need to get up to speed in physics in order to embark on their degree course. As different courses have different starting points, the text is subdivided into sections and each of the first few sections are written to offer different "jumping off" points. Adopting a lively approach, the author uses worked examples and references to practical experiments to support the facts, supplementing these with exercises and self-test questions. Additionally, each chapter starts with a list of objectives and ends with summary points to reinforce the core themes discussed in that chapter and provide a systematic framework for building skills. This is a text for Access and Foundation (Year 0) science students and undergraduate students on science, engineering or medicine courses without A level Physics.